The Impact of Entrepreneurial Spirituality on Business Performance: Based on the Survey of Private Enterprise Executives in Fujian China - Lin, Huiling; Fang, Weiqiong; Wei, Guojiang (Frontiers in Psychology, 2022)
Entrepreneurship is the main engine of economic development. This paper aims to explore the impact of high executives’ entrepreneurial spirituality (ES) on the business performance in China under the background of “mass entrepreneurship and innovation.” By analyzing the relevant literature of entrepreneurship, the connotation and elements of ES are determined. According to the relevant research, we design the questionnaire of ES and business performance. The questionnaire was distributed to 100 private enterprise entrepreneurs by equidistant sampling, and 74 valid questionnaires were recovered. According to the questionnaire, responsibility has the highest score, followed by innovation, proactiveness, and risk-taking. The ES of women is slightly higher than that of men. The entrepreneurs with higher education also have higher score in ES. After analyzing the impact of different elements of ES on enterprise performance using structural equation modeling (SEM) and regression equation model, it is found that: (1) ES has a positive impact on enterprise performance. (2) Different factors of ES have different effects on business performance, and innovation and proactiveness play the greatest role. (3) There is an inverted U-shaped relationship between innovation, risk-taking, and business performance.